Principles and benefits of UX strategy : an introduction to business strategy, valuation innovation, and validating a value proposition (O'Reilly, 2016)
"This course is part one of user experience (UX) pro Jaime Levy’s five part series on UX strategy. It presents a solid framework on the practice of UX strategy and its role in crafting innovative products. Tailored for entrepreneurs, start-up founders, business executives, digital product managers, and UX/UI designers, this video offers an example filled exploration of UX strategy as the must-have nexus between business strategy and UX design."--Resource description page.